2019
DOI: 10.1108/ijoa-07-2019-1837
|View full text |Cite
|
Sign up to set email alerts
|

Perceived contract violation and job satisfaction

Abstract: Purpose This paper aims to investigate how employees’ perceptions of psychological contract violation or sense of organizational betrayal, might diminish their job satisfaction, as well as how their access to two critical personal resources – emotion regulation skills and work-related self-efficacy – might buffer this negative relationship. Design/methodology/approach Two-wave survey data came from employees of Pakistani-based organizations. Findings Perceived contract violation reduces job satisfaction, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The risk that employees’ frustrations with politicized decision-making translate into negative work-related feelings and behaviours is amplified to the extent that they also ruminate on the influences of uncontrollable, external crises on their work (De Clercq and Pereira, 2021b). Even if this study did not directly assess employee skills, this risk likely can be contained if employees can leverage pertinent skills to cope with the dual hardships, such as creative self-efficacy (Christensen-Salem et al , 2021), emotion regulation (De Clercq et al , 2021a) or resilience (Caniëls and Hatak, 2022). Highly politicized organizations that also face external crisis threats accordingly could benefit from formal training programs or on-the-job-training initiatives that nurture such skills (Ahadi and Jacobs, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The risk that employees’ frustrations with politicized decision-making translate into negative work-related feelings and behaviours is amplified to the extent that they also ruminate on the influences of uncontrollable, external crises on their work (De Clercq and Pereira, 2021b). Even if this study did not directly assess employee skills, this risk likely can be contained if employees can leverage pertinent skills to cope with the dual hardships, such as creative self-efficacy (Christensen-Salem et al , 2021), emotion regulation (De Clercq et al , 2021a) or resilience (Caniëls and Hatak, 2022). Highly politicized organizations that also face external crisis threats accordingly could benefit from formal training programs or on-the-job-training initiatives that nurture such skills (Ahadi and Jacobs, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An important driver of OCB is the extent to which employees feel satisfied with their job (Bowling, 2009). For example, a recent study found that employees' job satisfaction can enhance their willingness to perform positive work activities (De Clercq et al, 2019). A meta-analysis also confirmed the positive relationship between job satisfaction and OCB (LePine et al, 2002).…”
Section: Job Satisfaction As a Mediatormentioning
confidence: 95%
“…job satisfaction, effective commitment, turnover intentions) (Pate et al, 2003;Zhao et al, 2007). On the other hand, the correlation between perceived contract violation and low job satisfaction was found to be weaker as the workrelated self-efficacy increased (De Clercq et al, 2019). Therefore, it is necessary to study the mitigating role of self-efficacy on the negative effects of PCB.…”
Section: Intrinsic Motivationsmentioning
confidence: 99%